Dramaturgi Peluncuran Danantara dan Dampaknya terhadap IHSG dalam Perspektif Politik Ekonomi - Rusli, Urisnawati; Masnia, Masnia; Darmawati, Darmawati; Rasyid, Syarifuddin (Journal of Business and Economics Research (JBE), 2025)
This study analyzes the launch of the Indonesian Sovereign Wealth Fund, Daya Anagata Nusantara Investment Authority (Danantara), through Erving Goffman's dramaturgical approach, focusing on its impact on the Indonesia Stock Exchange Composite Index (IHSG). Using a qualitative method, the study identifies the government's narrative through the "front stage" of public communication, as well as media and investor responses as the "audience." Data were collected through documentation techniques, mass media analysis, social media, and online observation (netnography), including official speeches, online news, and other digital content. The findings reveal a tension between political symbolism and transparency, which influences market perception. The short-term negative reaction in the IHSG reflects a misalignment between public image and policy reality. This study recommends the importance of coherence between symbolic communication and governance in maintaining market stability and building investor trust.